Prevalence of schistosomiasis mansoni in indigenous Maxakali villages, Minas Gerais, Brazil - Nacife, Maria Beatriz Pena e Silva Leite; Siqueira, Liliane Maria Vidal; Martins, Rafael; Vianna, Valeska Natiely; Barbosa, Keila Furbino; Masioli, Cássio Zumerle; Silva, Jaime Costa da; Machado-Coelho, George Luiz Lins (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Intestinal parasitic infections are a common health problem among Amerindian populations and schistosomiasis represents one of the most prevalent diseases in Maxakali people. The Kato-Katz is the diagnostic method recommended by WHO for epidemiological studies; however, one of the technique’s limitations is the failure to detect parasites in individuals with low parasite load. The aim of this study was to establish the prevalence of Schistosoma mansoni in indigenous Maxakali villages, evaluating the TF-Test® performance for diagnosis compared to the Kato-Katz technique. Stool samples from 545 individuals were processed by the TF-Test® (1 sample) and Kato-Katz (1 slide). The positivity rate for S. mansoni by Kato-Katz was 45.7%. The rate by the TF-Test® was 33.2%, and 51.9% by the combined parasitological techniques. The amplitude of parasite load was 24 to 4,056 eggs per gram of feces (epg), with a geometric mean of 139 epg. The co-positivity, co-negativity, and accuracy values by TF-Test® in relation to Kato-Katz were 59.0%, 88.5%, and 75.0%, respectively. The agreement between these techniques was moderate (k=0.486) as determined by the kappa index. Thus, the results of this study demonstrated that the performance of Kato-Katz was superior (p